Protective effects of in vitro treatment with zinc, d-aspartate and coenzyme q10 on human sperm motility, lipid peroxidation and DNA fragmentation - Talevi, Riccardo (BioMed Central, 2013)
BACKGROUND: Spermatozoa are extremely vulnerable to oxidative stress caused by the unbalance between concentrations of reactive oxygen species and antioxidant scavenging systems present inside the male reproductive tract. In spite of a large number of clinical studies that claimed the beneficial effects of antioxidant oral administration on sperm physiology and fertility, only a few studies were addressed to evaluate their effects on spermatozoa in vitro. Main aims of the present study were to assess the influence of zinc, D-aspartate and coenzyme Q10, included in the dietary supplement Genadis (Merck Serono), on human sperm motility, DNA fragmentation and lipid peroxidation. METHODS: Semen samples, obtained from forty-four patients (23–30 years of age) were enrolled in this study, twenty-four were normospermic and twenty patients were oligospermic. Semen samples were analysed for sperm progressive motility and kinetics through computer assisted analysis, DNA fragmentation and lipid peroxidation. RESULTS: Main results showed that in both normo and oligospermic samples, total and progressive sperm motility is maintained by in vitro treatment with zinc, D-aspartate and coenzyme Q10, whereas a significant decrease of these parameters occurs in parallel samples incubated in medium alone. Zinc, D-aspartate and coenzyme Q10 also prevented the decrease of sperm kinetics but such an effect was highly significant only in oligospermic samples. Moreover, they also protected spermatozoa by the increase of DNA fragmentation and lipid peroxidation. CONCLUSIONS: Zinc, D-aspartate and coenzyme Q10 exert a direct protective effect on human spermatozoa preventing the decrease of motility and the increase of DNA fragmentation and lipid peroxidation during in vitro culture.